2022
DOI: 10.1108/itse-11-2021-0202
|View full text |Cite
|
Sign up to set email alerts
|

Predicting students’ continuance use of learning management system at a technical university using machine learning algorithms

Abstract: Purpose This study aims to investigate factors that could predict the continued usage of e-learning systems, such as the learning management systems (LMS) at a Technical University in Ghana using machine learning algorithms. Design/methodology/approach The proposed model for this study adopted a unified theory of acceptance and use of technology as a base model and incorporated the following constructs: availability of resources (AR), computer self-efficacy (CSE), perceived enjoyment (PE) and continuance int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 67 publications
(187 reference statements)
1
13
0
Order By: Relevance
“…Based on profile and prediction analyses, educators and universities, in general, may deploy nudging intervention systems, control drop-out and retention rates, monitor student trajectories, and guide them to academic success [117]. Moreover, using machine learning algorithms, it is possible to predict the use of learning resources, adoption behavior, and integration in the educational process [62,104], and systematize the academic evaluation process [89,146].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on profile and prediction analyses, educators and universities, in general, may deploy nudging intervention systems, control drop-out and retention rates, monitor student trajectories, and guide them to academic success [117]. Moreover, using machine learning algorithms, it is possible to predict the use of learning resources, adoption behavior, and integration in the educational process [62,104], and systematize the academic evaluation process [89,146].…”
Section: Discussionmentioning
confidence: 99%
“…Most frequently, the 21 publications centered on the application of AI relied on machine learning and data mining algorithms. This trend of classification, modeling, prediction, determining satisfaction of students, and quality of learning experience was found in eight papers focused on no particular domain [47,61,86,[104][105][106][107]. From this group, Ali et al [108] developed a mechanism that intelligently predicted the appropriate preferences for virtual assistance and course selection for Agriculture, Mathematics, and Computer sciences students.…”
Section: Profile and Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study contributed to the literature in several ways. Although scholars have studied satisfaction and continuance intention in various contexts such as a learning management system (Kuadey et al. , 2022), health apps (Yan et al.…”
Section: Discussionmentioning
confidence: 99%
“…The study contributed to the literature in several ways. Although scholars have studied satisfaction and continuance intention in various contexts such as a learning management system (Kuadey et al, 2022), health apps (Yan et al, 2021a, b), and volunteer jobs (Bang, 2015), determinants of satisfaction and continuance intention have received less attention in retail apps context. This study tested IS success model in the retail context and showed the power of this theory in explaining satisfaction and continuance intention towards retail apps.…”
Section: Theoretical Implicationsmentioning
confidence: 99%